Thermal and Mechanical Properties of Nano-TiC-Reinforced 18Ni300 Maraging Steel Fabricated by Selective Laser Melting - Francisco F. Leite; Indrani Coondoo; João S. Vieira; José M. Oliveira; Georgina Miranda (Journal of Manufacturing and Materials Processing)
Additive manufacturing (AM) has brought new possibilities to the moulding industry, particularly regarding the use of high-performance materials as maraging steels. This work explores 18Ni300 maraging steel reinforced with 4.5 vol.% TiC nanoparticles, fabricated by Selective Laser Melting (SLM), addressing the effect of post-fabrication aging treatment on both thermal and mechanical properties. Design of Experiments (DoE) was used to generate twenty-five experimental groups, in which laser power, scanning speed, and hatch distance were varied across five levels, with the aim of generating conclusions on optimal fabrication conditions. A comprehensive analysis was performed, starting with the nanocomposite feedstock and then involving the microstructural, mechanical, and thermal characterisation of SLM-fabricated nanocomposites. Nanocomposite relative density varied between 92.84% and 99.73%, and the presence of martensite, austenite, and TiC was confirmed in the as-built and heat-treated conditions. Results demonstrated a hardness of 411 HV for the as-built 18Ni300-TiC nanocomposite, higher than that of the non-reinforced steel, and this was further increased by performing aging treatment, achieving a hardness of 673 HV. Thermal conductivity results showed an improvement from ~12 W/m·K to ~19 W/m·K for nano-TiC-reinforced 18Ni300 when comparing values before and after heat treatment, respectively. Results showed that the addition of TiC nanoparticles to 18Ni300 maraging steel led to a combined thermal and mechanical performance suited for applications in which heat extraction is required, as in injection moulding.